Effect of jumping timing on result height for lift in synchronised swimming - Nakashima, M.; Hatakeyama, G.; Homma, Mi.; Ito, K. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
The objective of this study was to clarify the effect of jumping timing on resultant height for lift in synchronised swimming by means of the computer simulation. The lift by four swimmers, which consists of one upper, one middle and two lower swimmers in the formation was analyzed in the present study. The body geometries and joint motions of the swimmers were put into the simulation model. The equations of motion for the translational movements of the four swimmers were solved computationally, and the jumping height of the upper swimmer was obtained. By virtually changing the timing of motion among swimmers in the simulation, a parameter study about the effect of jumping timing on resultant height was carried out. From the parameter study, following findings were obtained: lt is important to synchronise the jumping motions of the upper and middle swimmers. Both the earlier and later jumps by the upper swimmer result lower jumping height. The gain due to the synchronisation is 0.5-0.7 m. The synchronised motion causes significant increase in the hip joint torque of the upper swimmer. This increase, however, can be reduced by taking an appropriate position during jumping motion.